1990
DOI: 10.1016/s0006-3495(90)82354-7
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of local anesthetic inhibition of neuronal sodium currents. pH and hydrophobicity dependence

Abstract: This study assesses the importance of local anesthetic charge and hydrophobicity in determining the rates of binding to and dissociation from neuronal Na channels. Five amide-linked local anesthetics, paired either by similar pKa or hydrophobicity, were chosen for study: lidocaine, two tertiary amine lidocaine homologs, a neutral lidocaine homolog, and bupivacaine. Voltage-clamped nodes of Ranvier from the sciatic nerve of Bufo marinus were exposed to anesthetic externally, and use-dependent ("phasic") block o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0
1

Year Published

1993
1993
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 35 publications
2
35
0
1
Order By: Relevance
“…pH < 7.0), the penetration of local anesthetics into neuron is dramatically reduced by decrease of the non-ionized form. Accordingly, its effect on voltage-gated sodium channels is diminished in severe acidic conditions [47]. In contrast to its action on sodium channels, our studies showed that tetracaine still has significant effect on ASIC current at pH level as low as 4.5.…”
Section: Discussionmentioning
confidence: 81%
“…pH < 7.0), the penetration of local anesthetics into neuron is dramatically reduced by decrease of the non-ionized form. Accordingly, its effect on voltage-gated sodium channels is diminished in severe acidic conditions [47]. In contrast to its action on sodium channels, our studies showed that tetracaine still has significant effect on ASIC current at pH level as low as 4.5.…”
Section: Discussionmentioning
confidence: 81%
“…In the present study, however, the most hydrophobic molecules [i.e., compounds 5 and 6 (the relative increase in logD value being ϳ 0.5 per methylene unit)] had lower in vitro potencies and exhibited significantly faster dissociation rates from VGSCs than compounds 3 or 4. Differences in local anesthetic pK a values and hence the relative proportions of cationic and uncharged free amine forms, also can influence the extent and/or kinetics of inhibition of VGSCs (Chernoff and Strichartz, 1990). The calculated pK a value (Pallas; CompuDrug International, Inc., Sedona, AZ) for lidocaine is 8.03.…”
Section: Discussionmentioning
confidence: 99%
“…Since the LA receptor of Na + channels is situated within the permeation pathway accessible by permanently charged LA derivatives only from the intracellular surface [6], clinic applications of LAs with a tertiary amine moiety require that LA drugs first penetrate the membrane phase in their neutral (unprotonatcd) form. The neutral form may enter and exit its receptor site via the transmembrane segments of Na + channels from the lipid environment [12, 43]. Such a hydrophobic pathway through the membrane phase is not well defined and the significance of this direct hydrophobic pathway has not been evaluated but it may play an important role for a neutral LA drug, benzocaine.…”
Section: Modulated Receptor Hypothesismentioning
confidence: 99%